Uncommon Nail Involvement during Bullous Pemphigoid - Zaouak, Anissa (Skin Appendage Disord, 2021)
Bullous pemphigoid (BP) is the most frequent autoimmune blistering disorder. The immune reaction targets BP180 and BP230 antigens, 2 components of junctional adhesion complexes at the basement membrane zone. Clinical aspect includes multiple tense bullae on urticarial plaques of the skin. Although the nail apparatus may be affected by the immune process, nail changes have been rarely reported during BP. We report a case of a 72-year-old woman diagnosed with BP who subsequently developed a secondary nail loss of the 2 thumbs and the left middle finger. Also, she presented onycholysis of the fourth left finger with the aspect of roller-coaster of the proximal border at dermoscopy. Steroid therapy at high doses was ineffective and the nail atrophy was permanent.